Piano Trio in E-flat major, op. 1, no. 1 (André) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Offenbach am Main; Germany; Jean André, 2024)
Early edition of the Piano Trio in E-flat major, op. 1, no. 1, published by J. André.